2020
DOI: 10.1111/joor.13104
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Diagnostic Criteria for Temporomandibular Disorders for children aged 8‐12 years

Abstract: Background and Objective: Objective of this study was to determine whether the diagnostic accuracy of the Diagnostic Criteria for Temporomandibular Disorders (DC/ TMD) is sufficient for use among schoolchildren aged 8-12 years. Methods: This prospective cohort study on diagnostic accuracy with calibrated examiners was conducted among 533 children of both sexes aged 8-12 years, with and without TMD symptoms, selected randomly from the Rhein-Neckar district. Self-reporting of non-dental facial pain was used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
4
12
0
1
Order By: Relevance
“…Having a standardised protocol to assess Axis I and Axis II would improve the quality of the research as well as clinicians' ability to detect children and adolescents at higher risk of developing long‐lasting pain. The need for tools to assess TMD in children has been clear since the publication of at least two previous studies 59,60 . However, both analysed only DC/TMD Axis I, without including any Axis II assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a standardised protocol to assess Axis I and Axis II would improve the quality of the research as well as clinicians' ability to detect children and adolescents at higher risk of developing long‐lasting pain. The need for tools to assess TMD in children has been clear since the publication of at least two previous studies 59,60 . However, both analysed only DC/TMD Axis I, without including any Axis II assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The need for tools to assess TMD in children has been clear since the publication of at least two previous studies. 59,60 However, both analysed only DC/TMD Axis I, without including any Axis II assessments.…”
Section: Delphi Among Psychological Expertsmentioning
confidence: 99%
“…NSAIDs are contraindicated in patients with gastrointestinal di sorders or NSAID-sensitive asthma. (5) Most of the studies conducted to assess prevalence of TMDs concluded common observation that females and younger age groups are the most affected categories by these disorders (6)(7)(8)(9) Also several studies founded a higher TMDs prevalence among university students, especially medical and dental undergraduates. (10 -13) Several studies investigated the incidence of TMDs and its related factors among kids, teenagers, adults and the elderly, but there is little knowledge available regarding colleges' dental students who are subject to a high psychosocial and physical manifestations of tension and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The temporomandibular joint (TMJ) complex consists of bone, cartilage, muscles, ligaments, and associated neurovascular channels supplying to the structures [1]. The disorders arising from these structures are also complex in nature with varied presentations such as pain originating from bone and muscles; displacement of the cartilaginous disc, and degenerating conditions related to bony components [2]. As per the recent classi cation of TMD, the earlier mentioned conditions are known as pain related TMD and TMJ disorders respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the evaluating criterion was replaced with DC/TMD and studies were carried out in varied populations across different countries [13,14,17]. A common observation made in the past studies was the preponderance of TMD among females and in the younger age groups [2,8,9,15]. Previous studies have also pointed out the higher prevalence of TMD in university students, especially medical and dental undergraduates [13,14,18,19].…”
mentioning
confidence: 99%